Coexistence of Co doping and strain on arsenene and antimonene: tunable magnetism and half-metallic behavior. Issue 3 (3rd January 2018) - Zhou, Yungang; Cheng, Geng; Li, Jing
Abstract : Effectively modulating the magnetism of two-dimensional (2D) systems is critical for the application of magnetic nanostructures in quantum information devices. Abstract : Effectively modulating the magnetism of two-dimensional (2D) systems is critical for the application of magnetic nanostructures in quantum information devices. In this work, by employing density functional theory calculations, we found the coexistence of Co doping and strain can effectively control the spin states of arsenene and antimonene structures. Unstrained Co-doped arsenene (arsenene–Co) and Co-doped antimonene (antimonene–Co) structures are nonmagnetic while under a strain, the magnetic moments of both cases were abruptly increased to about 2 μ B . The emergence of magnetism can be reflected by the reduction of the interactions between Co and its neighboring atoms by the strain, which leads to the spin-splitting of Co-3d states. More importantly, we found that the transition of magnetism accompanies the modifications of the electronic properties of arsenene and antimonene so that under strain both structures can exhibit a novel half-metallic behavior. These results provide an effective pathway for the development of arsenene- and antimonene-based electronic devices by applying Co doping and strain.